The Influence Of Health Promotion On The Knowledge Of Women Of Fertilizing Age (WUS) In The Prevention Of Cervical Cancer In The Working Area Of The PUSKESMAS Purwodi II 2017 - Anggrahini, Yuriska; Novelia, Shinta; Aisyiah; Putri, Nazwita Dewi (International Health Sciences Journal, 2024)
Cervical cancer is a health problem that affects countries in the world, especially developing countries. In Indonesia, cervical cancer ranks second after breast cancer. Of the 33 provinces in Indonesia, the highest number of cervical cancer sufferers is in East Java, namely 21,313 cases with a mortality rate of 10.3%. Efforts to prevent cervical cancer are carried out by early detection of cervical cancer, but this is not widely known to the wider public. One method for disseminating information about preventing cervical cancer is through health promotion. This research was conducted to determine the effect of health promotion on WUS knowledge in preventing cervical cancer. This research took the form of a quasi-experiment with a non-randomized- pretest-posttest control group design. The population in this study was 823 WUS in the working area of the Purwodadi II Community Health Center, a sample of 40 respondents was taken. The sample was separated into two groups, namely the group that was given health promotion and the group that was not given health promotion. The instrument used to measure knowledge before and after health promotion was a questionnaire. Data were analyzed using the t-test. Based on the results of data analysis, the following were obtained: (1) there was a significant difference in the knowledge of WUS before and after being given health promotion (p= 0.000). (2) there is a significant difference in WUS knowledge between the experimental group and the control group (p= 0.000). Health promotion can increase knowledge in preventing cervical cancer. This health promotion can be applied in everyday life.